Feasibility of a Brazilian samba protocol for patients with Parkinson’s disease: A clinical non-randomized study - Tillmann A.C. (2020)
© 2020 Associacao Arquivos de Neuro-Psiquiatria. All rights reserved.Background: New protocols applied in the rehabilitation of Parkinson’s disease enable different action strategies for health professionals, as well as a new range of activities for these individuals. However, no valid samba protocol with activity prescription for this population was found in the literature. Objective: To investigate the feasibility of a Brazilian samba protocol in individuals with Parkinson’s disease. Methods: Twenty participants, mean age of 66.4±10.7 years, diagnosed with idiopathic Parkinson ‘s disease, divided into: experimental group that received the intervention of Brazilian samba dance classes (10 individuals); and control group that maintained their routine activities (10 individuals). For data collection, a divided questionnaire was used: General Information; Disability stages scale; Balance and Quality of Life. Results: During class implementation, there were no falls, as all dance activities adhered to the details of the protocol steps without any changes. On average, patients completed 82.7% of activities. After 12 weeks, the experimental group had improvements in the UPDRS global score, in daily activities, and on motor examination. There was also improvement in balance scores and in the mobility domain of the quality of life in the experimental group. Conclusion: The samba protocol seems to be feasible and safe for patients with PD. Moreover, it has pleasant characteristics and offers sufficient physical benefits for combination with drug treatment. There were also benefits in social relationships and as a possible rehabilitation tool in individuals with Parkinson’s disease.